2009
DOI: 10.1158/1055-9965.epi-08-0965
|View full text |Cite
|
Sign up to set email alerts
|

Etiologic Heterogeneity for Cervical Carcinoma by Histopathologic Type, Using Comparative Age-Period-Cohort Models

Abstract: Background: Cervical carcinomas comprise two main histopathologic types, squamous cell carcinomas and adenocarcinomas. Human papillomavirus (HPV) infections are causative for both types but the respective tumors may have different carcinogenic pathways. Methods: To assess potential etiologic heterogeneity of cervical cancer by histopathologic type, we examined invasive squamous cell carcinomas and adenocarcinoma cervical cancer incidence rates in the National Cancer Institute's Surveillance, Epidemiology, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 48 publications
1
21
0
Order By: Relevance
“…This population evidence of SOC heterogeneity was concordant with respective molecular constructs of type I and type II oncogenic pathways (2, 6); and further showed that age had a nonuniform biological effect on the incidence rates. Crossings of the age-specific incidence rates occurred near age 40 years, and fitting of data in recently improved APC models (26,31) was crucial in demonstrating that the agedependent rate differences by grade were not driven solely by secular cohort or calendar period factors during the 16-year span examined (1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This population evidence of SOC heterogeneity was concordant with respective molecular constructs of type I and type II oncogenic pathways (2, 6); and further showed that age had a nonuniform biological effect on the incidence rates. Crossings of the age-specific incidence rates occurred near age 40 years, and fitting of data in recently improved APC models (26,31) was crucial in demonstrating that the agedependent rate differences by grade were not driven solely by secular cohort or calendar period factors during the 16-year span examined (1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005).…”
Section: Discussionmentioning
confidence: 99%
“…Our 17 4-year age groups and 4 4-year calendar periods spanned 20 4-year birth cohorts (i.e., 1909 to 1985, designated by mid-year of birth). As previously detailed, we used the age-period-cohort (APC) "fitted" age-at-onset curve to provide an estimate of the age-specific incidence rate, coordinately adjusted for both calendar-period and birth cohort effects (26,31).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet the risk of CIN3ϩ after one-time detection of HPV18 was substantially higher than for the other HR-HPV genotypes in aggregate. HPV18 is strongly associated with adenocarcinoma and AIS, 22,23,36 which is on the rise in Western countries 37,38 and is preferentially missed by cytologic methods. 39 It is therefore rational to monitor for HPV18 as well as HPV16 separately in screening.…”
Section: -Year Cervical Cancer Riskmentioning
confidence: 99%
“…Jalilian et al (2011) reported perceived barriers as a significant predictor of undergoing Pap smear screening test and recommended strategies for reducing perceived barriers to undergoing the test (12). The results of a cross-sectional study by Reimers et al (2009) also showed that appropriate educational programs could reduce barriers to the Pap smear test through improving women's knowledge about the test (13). Schulmeister and Lifsey (1999) also concluded that appropriate educational interventions are needed for reducing the barriers to the Pap smear test (14).…”
Section: Discussionmentioning
confidence: 99%